STUDENT PERCEPTION STUDY ON SMART CAMPUS: A CASE STUDY ON HIGHER EDUCATION INSTITUTION - Mustafa, Mohd Faizal; Mohd Isa, Mohd Rizal; Abdul Rauf, Ummul Fahri; Ismail, Mohd Nazri; Mohd Shukran, Mohd Afizi; Khairuddin, Mohammad Adib; Wahab, Norshahriah; Mohd Safar, Noor Zuraidin (Malaysian Journal of Computer Science, 2021)
With the current development of science and technology, big data technology, the Internet of Things (IoT), cloud computing, and mobile Internet in Malaysia, it is time for smart campuses to be established and Higher Education Institution (HEI) should not have left behind. The smart campus is the upgraded version of a digital university, providing a better academic environment to the lecturers and students. A smart campus enhances education, research, design, and delivering the appropriate higher learning modules to pursue the latest developments in ICT technology that can drive future educational growth and innovation. In short, the smart university is to construct a safe and secure, stable, environmentally-friendly, and energy-saving campus. However, so far, there is no standard smart campus concept to follows. This research paper evaluates the student’s perceptions on the smart campus from the various application. A total of 912 students from local HEI have participated as valid observations for data analysis. The results show the students have selected 11 applications as high impact based on the Relative Importance Index for smart campus implementation. Future work could focus on the feedback from the staff and lecturers’ points of view to propose a solid conceptual smart campus framework.